PENGEMBANGAN MATERI SEJARAH KEBUDAYAAN ISLAM (SKI) PADA MADRASAH TSANAWIYAH - Abubakar, Istiâ€™anah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
History as the mother of science indicates the centrality of history as a science that plays an important role in the life and Bohemian. This important position needs to be tranferred through a process of learning, including learning history of Islamic culture. Ironically, history is a unwelcome subject and even almost considered a useless subject. One reason is thar the learning process is still textually. Learning procesess are less developed in balance 3 domain could be due to lack of understanding of the characteristic, the analysis of the material that is not done and learning strategies that are less precise. This paper will discuss the third case, so that the teaching of history is not just storytelling, but also able to present an exciting and meaningful learning. The goal is to position â€œ motherhoodâ€ in the scope of scientifiq history.